Dichotic multiple-frequency auditory steady-state responses in evaluating the hearing thresholds of occupational noise-exposed workers - Hsu, Ruey-Fen; Chen, Shun-Sheng; Lu, Sheng-Nan; Ho, Chi-Kung; Lin, Hsiu-Fen (The Kaohsiung journal of medical sciences, 2011)
An objective, fast, and reasonably accurate assessment test that allows for easy interpretation of the responses of the hearing thresholds at all frequencies of a conventional audiogram is needed to resolve the medicolegal aspects of an occupational hearing injury. This study evaluated the use of dichotic multiple-frequency auditory steady-state responses (Mf-ASSR) to predict the hearing thresholds in workers exposed to high levels of noise. The study sample included 34 workers with noise-induced hearing impairment. Thresholds of pure-tone audiometry (PTA) and Mf-ASSRs at four frequencies were assessed. The differences and correlations between the thresholds of Mf-ASSRs and PTA were determined. The results showed that, on average, Mf-ASSR curves corresponded well with the thresholds of the PTA contours averaged across subjects. The Mf-ASSRs were 20 ± 8 dB, 16 ± 9 dB, 12 ± 9 dB, and 11 ± 12 dB above the thresholds of the PTA for 500 Hz, 1,000 Hz, 2,000 Hz, and 4,000 Hz, respectively. The thresholds of the PTA and the Mf-ASSRs were significantly correlated ( r = 0.77–0.89). We found that the measurement of Mf-ASSRs is easy and potentially time saving, provides a response at all dichotic multiple frequencies of the conventional audiogram, reduces variability in the interpretation of the responses, and correlates well with the behavioral hearing thresholds in subjects with occupational noise-induced hearing impairment. Mf-ASSR can be a valuable aid in the adjustment of compensation cases.